SPEECH INFLUENCE: TYPES AND METHODS (Proceedings of Southern Federal University. Philology, 2013)
Pomirlianou N.A.Keywords: concept, practical psychology, pedagogy, influence strategy, ideological propaganda.The article deals with theoretical aspects of speech influence: the problem of the concept ‘speech influence’, the definition of manipulative speech influence, traditional ways of speech influence and corresponding types and methods. According to the research in psycholinguistics, practical psychology, pedagogy, influence strategy, ideological propaganda and practice in advertisement and arguments the author singles out methods which help to achieve speech influence.